SEX WORKERS LIVED EXPERIENCES OF STIGMA IN NAIROBI, KENYA - MUTISO, MOSES MUTUA; MASESE, ERIC; MASINDE, JAMIN (Advances in Social Sciences Research Journal, 2020)
Since immemorial sex work has been viewed as immoral in the society that we live in. This has made those who practise it to experience something traumatic in their life. Although sex work has been viewed by sex workers as a livelihood still the negative connotation associated with it has never faded. Similarly, studies on the stigma surrounding sex work industry are well documented and easily recognized worldwide. However, few studies examine the emic perspective of stigma among sex workers more so in Kenya. In the face of stigma, it makes sex workers adopt various strategies as a way of shading the stigma as they earn their livelihood. Using stigma narratives from 28 respondents practicing sex work, selected using purposive, snowball and direct sampling techniques, this paper shows sex work as a livelihood to sex workers and they use various means to sustain it despite the stigma they face in their everyday life. This ambiguity is evidenced by the strategies that sex workers use in resisting the perception of their work as immoral and evil and at the same time trying to (re)negotiate their threatened identity due to stigma within the larger community they live in. This paper then argues that stigma still remains a major social problem among those practising sex work despite the various constructions on sex work. This is evidenced from stigma narratives where the sex workers in Kenya are subject to various stigmatizing forces in their daily lives in their interactions with the family/relatives, neighbours, religious institutions, law enforcers, and health providers. These stigmas harm the sex workers’ health, both through apparent manifestations such as physical or verbal abuse and through subtler means such as those which generated or perpetuated vulnerability which then compel the sex workers to come with personal individualized ways or collective ways of dealing with stigma. To come up with development of interventions that may reduce stigma, it is important to understand the ways in which sex workers are stigmatized (manifestations of stigma), as well as who is doing the stigmatizing (sources of stigma) and its solution should be pegged on the various sources of stigma.